Pemeriksaan Parasit Anisakis Sp pada sarden kadaluarsa dan belum kadaluarsa - Prasetya, Arita Ajeng; Mahtuti, Erni Yohani; Masyhur, Muhammad (FORUM ILMIAH KESEHATAN, 2022)
Anisakis sp is a parasite that lives in fish and marine mammals, including mackerel in canned food such as sardines. Anisakis sp can infect humans if ingested and cause allergic reactions. This study aims to determine the description and differences in the number of parasites from the results of Anisakis sp parasite examination on expired and unexpired sardines. An analytical descriptive study with samples of 3 different brands of sardines for each type of sardines expired and not yet expired, namely samples A, B and M. The sampling technique was random sampling using the sedimentation method using NaCI solution with a lower specific gravity than parasitic organisms. so that the parasites can settle to the bottom. The macroscopic results showed that in expired samples, the presence of odor (highest 80%), mucus (highest 40%), mushrooms (highest 60%) and parasites Anisakis sp (highest 100%). Meanwhile, in the non-expired samples, the presence of odors (0% highest), mucus (0% highest), mushrooms (0% highest) and Anisakis sp parasites (20% highest). So it could be concluded that the condition of expired sardines will have a greater impact on damage, especially on the odor indicators, the presence of mucus, the presence of fungi and the presence of Anisakis sp. parasites.Keywords: Anisakis sp.; sardines; expired ABSTRAK Anisakis sp adalah parasit yang hidup pada ikan dan mamalia laut, termasuk ikan makarel pada makanan kemasan kaleng seperti sarden. Anisakis sp dapat menginfeksi manusia jika termakan dan menyebabkan reaksi alergi. Penelitian ini bertujuan untuk mengetahui gambaran dan perbedaan jumlah parasit dari hasil pemeriksaan parasit Anisakis sp pada sarden kadaluwarsa dan belum kadaluwarsa. Penelitian deskriptif analitik dengan sampel berupa 3 merk sarden yang berbeda setiap jenis sarden kadaluwarsa dan belum kadaluwarsa, yaitu sampel A, B dan M. Teknik pengambilan sampel adalah random sampling dengan menggunakan metode sedimentasi menggunakan larutan NaCI dengan berat jenis yang lebih rendah dari organisme parasit, sehingga parasit dapat mengendap di bawah. Hasil penelitian secara makroskopis menunjukkan bahwa pada sampel kadaluwarsa, keberadaan bau (tertinggi 80%), lendir (tertinggi 40%), jamur (tertinggi 60%) dan parasit Anisakis sp (tertinggi 100%). Sedangkan pada sampel tidak kadaluwarsa, keberadaan bau (tertinggi 0%), lendir (tertinggi 0%), jamur (tertinggi 0%) dan parasit Anisakis sp (tertinggi 20%). Maka bisa disimpulkan bahwa kondisi sarden yang kadaluwarsa akan lebih berdampak pada kerusakan, khususnya pada indikator bau, keberadaan lendir, keberadaan jamur dan keberadaan parasit Anisakis sp.Kata kunci: Anisakis sp.; sarden; kadaluwarsa